ANALYSIS OF INDONESIA SHARIA BANK'S HEALTH LEVEL ACCORDING TO FINANCIAL SERVICES AUTHORITY REGULATIONS - Kinanti, Sekar; Budiantoro, Harry; Gunawan, Andri; Lapae, Kanaya; Ningsih, Hestin Agus Tantri (I-Economics, 2024)
This study aims to determine and assess the Health Level of a bank using the Risk Profile, Good Corporate Governance, Earnings and Capital (RGEC) method of Bank Syariah Indonesia Quarter I 2021 - Quarter III 2022. This type of research is quantitative. The analysis used in this study uses Net Financing Performance (NPF), Financing to Deposit Ratio (FDR), Operating Expenses and Operating Income (BOPO) and Net Operating Margin (NOM). This study will compare and analyze the health level of banks at Bank Syariah Indonesia. Based on the research results, it can be concluded that Bank Syariah Indonesia for the NPF ratio shows an assessment of the bank's health level, namely "Healthy", FDR Bank Syariah Indonesia for the first quarter of 2019 - the fourth quarter of 2020 before the merger was still at an average of "fairly healthy", the NOM ratio of Bank Syariah Indonesia is still below 0, not yet capable of managing all of its productive assets and the health level of the CAR ratio is still at rank 1 "Very Healthy "because according to the provisions of the bank's health level if CAR> 12% then it is said to be "Very Healthy".